Percepcja wzajemnych relacji w układzie "teściowa-synowa" = Perceptions of personal qualities of daughters-in-law and mothers-in-law - Kulikov, Leonid V.; Petrova, Dari'a K. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the study is to explore the social representations of the current and the ideal relationship between the daughters-in-law and mothers-in-law. Discussed carried out by the questionnaire data. It has been found that the presentation of the partners of each other in a dyad daughters-in-law - mothers-in-law have notable differences. In most cases, mother-in-law said that her daughters-in-law sees her more positive qualities than negative. Daughter-in-law believes mothers-in-law sees it as more negative attributes than positive. The study helped to clarify the cause of the opposite and symmetrical negative perceptions about the personal qualities of a partner in a dyad. Mother-in-law and daughter-in-law compete for emotionally charged interpersonal interaction with close person (son/husband).
Keywords: style relacji interpersonalnych; więzi rodzinne; bliskość emocjonalna; synowa; teściowa; interaction style; family relationship; emotional closeness; mothers-in-law and daughters-in-law